Implementation of The Government Policies in The Performance of Merdeka Belajar Kampus Merdeka Program at Public Administration Study Program of Muhammadiyah University Makassar - Nur Wahid; Sitti Rahmawati Arfah; Indri Apriani Nur (Universitas Muhammadiyah Gorontalo, 2022)
Merdeka Belajar Kampus Merdeka (MBKM) program becomes one of the studies about policy which being held by the government to be applied to higher education. The key to a successful implementation of the MBKM policy in university is by changing the mindset into a curriculum based on adaptive and flexible learning achievement.The research method is a qualitativeresearch to determine the key informants, researchers use purposive and snowball techniques, and data collection techniques include in-depth interviews, observation, and documentation. The results indicated that the MBKM program regulation in the study program still experience some complications, such as in converting subjects and also the curriculum into a MBKM curriculum, coordinating the time difference at the beginning of the lectures with the form of learning activities, the hardship in partnering for cooperation and carrying out activities outside the study program, amount of programs and activities that must be done in a short time and simultaneously and also The MBKM implementing partners who limit the number of students acceptation at the location of the internship program and developing villages. In terms of strategic preparation, there are still insufficient resources, human resources that support the system, field supervisors and the low motivation of students to take part in the MBKM program